2009
DOI: 10.1001/archoto.2009.153
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Residual Neck Disease in Patients With Oropharyngeal Squamous Cell Carcinoma Treated With Radiation Therapy

Abstract: In conjunction with other clinical parameters, p16 status can help predict the need for post-RT ND in patients with OP-SCCA. Although close observation may be warranted in selected patients with p16+ tumors, patients with p16- tumors are at much higher risk for residual neck disease, even when initial nodal disease is less advanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…According to a recent investigation patients with HPVrelated tumors are less likely to have a pathological positive PND [55] but a positive PND represents a biological unfavorable subset of the HPV population with reduced survival possibly attributable to distant metastases [56].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent investigation patients with HPVrelated tumors are less likely to have a pathological positive PND [55] but a positive PND represents a biological unfavorable subset of the HPV population with reduced survival possibly attributable to distant metastases [56].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Patients with T1-2 p16ϩ tonsillar SCC presented with radiographic evidence of contralateral nodal spread with an incidence of 25.0% compared with 0% for p16Ϫ tumors (P ϭ 0.05), despite having no clinical or radiographic evidence of invasion outside the tonsillar fossa into tissues that have bilateral lymphatic drainage, such as the soft palate or base of tongue. This incidence of contralateral nodal spread is higher than what prior studies have reported for patients with early tonsillar primaries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite current data showing a difference in prognosis for patients with HPVϩ disease in smokers and nonsmokers, our dataset was too small to show a difference. 14 Our aim in publishing this initial data is to report the early observational difference in spread patterns among early-stage tonsillar SCC in p16ϩ versus p16Ϫ disease at our institution. Clearly, this information may change treatment recommendations if validated in a larger cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV status might be also considered in the indication of adjuvant therapy. It has been shown that p16 status as surrogate marker of HPV infection together with other clinical parameters successfully predicted the need of neck dissection after radiotherapy [42].…”
Section: Clinical Impactmentioning
confidence: 99%